Molecular Diagnostic of Toxoplasma gondii from Placental of Aborted Women in Mosul city (NTU Journal of Agriculture and Veterinary Science, 2023)
Toxoplasmosis is one of the most important parasitic diseases spread all the world. It is caused by the Toxoplasma gondii parasite that infects mammals such as humans and animals that are intermediate hosts for this parasite. In this study,about 25 placental samples were collected from aborted women infected with Toxoplasmosis, From Al-Salam Teaching Hospital i Mosul city examaind microscopally, molecular and serological methods were used to diagnoses the infection in each sample .The results of this study recorded an infection rate of 100% in all placenta samples that were examined microscopically, The results of the molecular detection by convential polymerase chain reaction of the placenta samples, showed that the infection rate was 48% (12 samples out of 25), and following the data from infected women, it was noted that the age group (21-30) years was the most group has been infected. The results showed a closeness of 100% to the chain of nitrogenous bases of the isolates that were recorded during this study, the alignment analysis showed a 100% relationship with each of the Iranian isolates MK507731, the Mexican KX270373, the Egyptian OP991839 and the Saudi LN714499, and a number of isolates registered in Iraq.